Metode Pembelajaran Keterampilan Berbicara Bahasa Arab di MAN 1 Metro, Lampung - Nurul Daroeni; Walfajri; Khotijah (Al-Ma‘rifah, 2020)
This study aims to determine how the learning method is a very important factor in learning foreign language speaking skills, especially Arabic. The method used in this research is the descriptive qualitative method. The object of this research is Madrasah Aliyah Negeri (MAN) 1 Metro, Lampung. Meanwhile, the instruments in this study were interviews and literature studies. It can be noted that the learning method greatly influences the learning process and outcomes. The results of this study indicate that the learning method used in MAN 1 Metro, Lampung, is the direct method (mubāsharah). The effectiveness and efficiency of this method can be proven in learning activities for vocabulary development, the practice of Arabic in daily communication, the practice of Arabic speech, and Arabic drama, and the use of Arabic vocabulary in public facilities. However, this is also not free from inhibiting factors, namely the background of educators who do not have an Arabic education background and a lack of competence as an Arabic teacher, students who are less motivated in learning Arabic, the background of students who do not understand Arabic, as well as teaching materials that are less relevant for students to use in learning Arabic speaking skills.